1990
DOI: 10.1109/16.106255
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and design of field emitters

Abstract: Electron emission characteristics are described for two generic field emitter structures: a cone and a wedge. Effects of variations in emitter geometry on electron current, spectral and temporal dispersion of eletron emission, and emitter heating are calculated analytically and by computer simulation. Several guidelines for emitter design are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Structural feature of materials affects some defining characteristics during the field electron emission process, including the field enhancement factor, local electronic field distribution, as well as actual emission sites and emission area. [22] And hence, it is of important significance to simulate and analyze the field emission structures and their corresponding emission properties. In this work, we focused on vertical tapered nanostructure and its derivative wedged ordered nanostructure.…”
Section: Doi: 101002/aelm201700295mentioning
confidence: 99%
“…Structural feature of materials affects some defining characteristics during the field electron emission process, including the field enhancement factor, local electronic field distribution, as well as actual emission sites and emission area. [22] And hence, it is of important significance to simulate and analyze the field emission structures and their corresponding emission properties. In this work, we focused on vertical tapered nanostructure and its derivative wedged ordered nanostructure.…”
Section: Doi: 101002/aelm201700295mentioning
confidence: 99%
“…Numerous more rigorous treatments all leading to the same conclusions can be found in the literature. See for example the work of Marcus et al [14], Zaidman et al [15], Temple et al [16], Jensen et al [17], and Kang et al [18].…”
Section: The Original Spindt-cathode Fabrication Processmentioning
confidence: 99%
“…Thus, many efforts have been made on the development of new emitters with improved emission properties, including the evaluation techniques for such emitters. [2][3][4][5] Some of the present authors have extensively carried out electron holography measurements, which is a unique tool for quantitatively visualizing the electric field on a nanometer scale, on the various types of field emitters. In the previous studies, by means of electron holography, we have reported on not only evaluation techniques for the emitters in the presence of an applied voltage but also a useful method to obtain quantitative information on the microfields around the emitters.…”
Section: Introductionmentioning
confidence: 99%